2021
DOI: 10.1021/acs.est.1c02985
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Routes of the Microbiome and Resistome from Manure to Soil and Lettuce

Abstract: The land application of animal manure can introduce manure microbiome and resistome to croplands where food crops are grown. The objective of this study was to characterize the microbiome and resistome on and in the leaves of lettuce grown in manured soil and identify the main transmission routes of microbes and antibiotic resistance genes (ARGs) from soil to the episphere and endosphere of lettuce. Shotgun metagenomic results show that manure application significantly altered the composition of the microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 53 publications
(113 reference statements)
4
29
0
Order By: Relevance
“…A growing concern about the application of untreated animal manure to agricultural soil is the possibility of contamination with pathogenic ARB and antibiotic resistance genes (ARGs), as animal manure is considered a significant reservoir of both enteric and pathogenic ARB and ARGs (Robins-Browne, 2005;Johnson et al, 2016). Previous studies that investigated the impact of animal manure on soil resistome demonstrated that fertilisation with animal manure resulted in the appearance or increased level and diversity of ARB and ARGs in soils (Jensen et al, 2013;Chen et al, 2016b;Fatoba et al, 2021;Sun et al, 2021). Jensen et al (2013) reported the appearance of E. coli in soil after the application of animal slurry to three Danish agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing concern about the application of untreated animal manure to agricultural soil is the possibility of contamination with pathogenic ARB and antibiotic resistance genes (ARGs), as animal manure is considered a significant reservoir of both enteric and pathogenic ARB and ARGs (Robins-Browne, 2005;Johnson et al, 2016). Previous studies that investigated the impact of animal manure on soil resistome demonstrated that fertilisation with animal manure resulted in the appearance or increased level and diversity of ARB and ARGs in soils (Jensen et al, 2013;Chen et al, 2016b;Fatoba et al, 2021;Sun et al, 2021). Jensen et al (2013) reported the appearance of E. coli in soil after the application of animal slurry to three Danish agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…in agricultural soil following chicken litter application. Another study from the United States showed that manure application significantly increased the diversity of surface soil microbiome and resistome and also introduced tetracycline and sulphonamide resistance genes to the soil (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms in the soil play significant roles in plant development(Sheng et al, 2021; Sun et al, 2021; Warmink and van Elsas, 2009; Zhao et al, 2014). They are an essential component of soil ecology and serve as an important mechanism for soil regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological variations in plants may result from growth in soil with different fertilizer concentrations (Sun et al 2021).…”
Section: Nitrogen Influenced Plant Growth By Hitchhikingmentioning
confidence: 99%
“…Recently, it was reported that microbes could be transmitted not only from plants to animals, but also from animals to plants. Lettuce grown in soil containing cattle manure, acquired in their leaves manure-borne microbes that include antibiotic resistance genes, which may assist in protection against infection [215]. Moreover, antibiotic resistance genes, acquired from poultry litter was present in the roots of lettuce [216].…”
Section: Horizontal Transmissionmentioning
confidence: 99%